Treg cells as a protective factor for Hashimoto`s thyroiditis: a Mendelian randomization study - Guo, Jinzhou; Si, Gao; Si, Fuchun (Frontiers in Endocrinology, 2024)
Background and objectives Hashimoto's thyroiditis (HT), a chronic autoimmune disorder impacting thyroid function, is a growing public health concern. The relationship between Treg cells and HT has been extensively studied, with Treg cells considered crucial in suppressing HT progression. However, these studies have mainly been observational, limiting our understanding of Treg cells' impact on HT risk. Leveraging large datasets, we utilized Mendelian randomization (MR) analysis to examine the causal association between Treg cell biomarkers and HT, providing additional validation for these relationships. Methods Comprehensive two-sample Mendelian randomization analysis was performed to determine the causal association between Treg cells signatures and HT in this study. Based on publicly available genetic data, we explored causal associations between 165 Treg cells signatures and HT risk.The European cohort study has identified five Treg cell phenotypes that causally protect against HT risk. Resting Treg %CD4 (OR = 0.975, 95% CI = 0.954~0.998, P = 0.030) ; CD4 on resting Treg (OR = 0.938, 95% CI = 0.882~0.997, P = 0.041; CD28-CD8dim %CD8dim (OR = 0.983, 95% CI = 0.969~0.998, P = 0.030); CD25 on CD39+ resting Treg (OR = 0.926, 95% CI = 0.864~0.991, P = 0.026); 5) CD28 on activated & secreting Treg (OR = 0.969, 95% CI = 0.942~0.996, P = 0.025). The Asian cohort study has identified four Treg cell phenotypes negatively correlated with the risk of HT. CD25hi %T cell (OR = 0.635, 95% CI = 0.473~852, P = 0.002) ; CD4 Treg %CD4 (OR = 0.829, 95% CI = 0.687~1.000, P = 0.050); CD127-CD8br %T cell (OR = 0.463, 95% CI =0.311~0.687, P < 0.001) ; CD3 on resting Treg (OR = 0.786, 95% CI = 0.621~0.994, P = 0.044). Conclusions Our study has demonstrated the close connection between Treg cells and HT by genetic means, thus providing foundational basis for future research.